Unsteady MHD thermally conducting thin film flow of a third grade fluid between two oscillating moving vertical belts. - Nirmala P. Ratchagar, C. Surya, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
Study about the MHD unsteady third grade thin film fluid flow in an oscillating two parallel moving belts. The moving vertical belts are oscillating and liquid drain down due to the gravity. Resulting fluid flow, thermal and mass transfer processes appearing in the third grade fluid are described by system of coupled non-linear equations are solved using suitable perturbation method. Numerically outputs are obtained graphically portrayed and the important characteristics parameters are discussed.